SOSIALISASI BAHAYA DIARE TERHADAP KESEHATAN PADA SISWA / i MTSN 7 ACEH BESAR - Mhd Hidayattullah; Zakia Ulrahmah; Nur Mulia (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Diarrhea is a bowel movement with a mushy or liquid consistency, it can even be water alone with a frequency more often than usual (three times or more) in one day. diarrhea can cause system disorders or complications that are very dangerous for sufferers. Some of them are disorders of fluid and electrolyte balance, hypovolemia shock, disruption of various organs, and if not handled properly can cause death. Diarrhea most often affects children under five years old. Based on data obtained from the World Health Organization (WHO) in 2019, more than a third of global child deaths were caused by diarrhea as much as 35%.